Dysregulation of the Wnt pathway in adult eosinophilic esophagitis. Issue 8 (1st December 2015) - Giannetti, M.; Schroeder, H. A.; Zalewski, A.; Gonsalves, N.; Bryce, P. J.
Summary: Eosinophilic esophagitis (EoE) is a chronic inflammatory disease characterized pathologically by eosinophil infiltration. In addition to loss of barrier integrity, a dominant T Helper 2-associated immune response and strong allergic connection, the esophagus tissue undergoes dramatic changes, with frequent presence of mucosal rings, strictures, linear furrows, and trachealization. Although the inflammatory mechanisms behind this disease are being increasingly well understood, the structural features remain unexplained. We examined the expression of key members of the Wnt-signaling pathway in biopsies from patients with EoE. This pathway has been shown to be critically important in regulating cellular homeostasis, growth, and differentiation and to be dysregulated in several disease conditions. Biopsies from adult EoE patients were collected by endoscopy and mRNA extracted. After cDNA synthesis, the relative gene expression from key upstream (secreted frizzled-related protein 1) and downstream (c-myc and Cyclin D1) molecules in the Wnt pathway, as well as several Wnt pathway members (Wnt1, Axin1, low-density lipoprotein receptor-related protein 6, glycogen synthase kinase 3 beta, and β-catenin), were determined. Biopsies from patients with EoE displayed significantly higher expression of secreted frizzed-related protein 1 than controls, as well as reductions in Cyclin D1 and c-myc. In contrast, there were no differences in the Wnt pathway molecules. The levels of expression of Cyclin D1 and c-myc, as well as β-catenin, in EoE patients showed strong correlations with the frequency of esophageal eosinophils. Our findings suggest that although there are no changes in the overall levels of key Wnt pathway genes in adult EoE, there is evidence for dysregulation of upstream and downstream regulators of Wnt signaling. Importantly, the associations with eosinophilia suggest that these may participate in the pathogenesis of this disease and be markers of disease severity.